Leah's Garden: Fields of Bounty - Book 3 - Snelling, Lauraine; Giron, Kiersti (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2023)
"Lilac Nielsen must learn to balance her new courtship with the young reverend and her pursuit of another dream-the publication of her artwork in a New York newspaper. But when a family crisis back in Ohio shakes the Nielsen sisters, can they continue the new life they've begun in Nebraska? And will Lilac be prepared for what God has in store for her future?"--
Keywords: Sisters -- Fiction; Women artists -- Fiction; Man-woman relationships -- Fiction; Nebraska -- Fiction; Romance fiction